Relationships between indices of sedentary behavior and hedonic well-being: A scoping review. (May 2021) - Sui, Wuyou; Sui, Anna; Prapavessis, Harry
Abstract: Background: Subjective well-being (SWB) holds positive implications for an individual's self-rated and objective health. Hedonic well-being, specifically, conceptualizes ideal SWB as optimizing one's affect and life satisfaction; as such, identifying health behaviors that can modify SWB is of importance. Notably, associations between indices of SB and outcomes of hedonic well-being are conflicting. Objectives: To synthesize, describe, and map existing evidence examining the relationship(s) between device-based and subjective indices of SB (i.e., SB, physical inactivity, and screen time) and outcomes of hedonic well-being (i.e., affect, life satisfaction, and overall hedonic well-being). Eligibility criteria: Included studies were peer-reviewed journal articles or thesis dissertations; (ii) published from earliest database entry year to May 29th, 2019; (iii) included a measure of SB or index of SB (i.e., physical inactivity, screen time); (iv) included a measure of hedonic well-being or outcome of hedonic well-being (i.e., affect, life satisfaction, hedonic well-being); (v) examined a relationship between some index of SB and some measure of hedonic well-being; and (vi) were written in English. Sources of evidence: PubMed, SCOPUS, Web of Science, PsycINFO, Nursing and Allied Health Database, CINAHL, SPORTDISCUS, and Physical Education Index databases were searched. The reference lists of pertinent reviews and articles were also scanned for relevant articles. Charting methods: Screening calibration was performed before studies were parsed for relevant data regarding the primary outcomes and descriptive characteristics. Results: Forty-six articles were included in the present review. The majority of studies were mainly cross-sectional (58.70%) and examined either physical inactivity (36.96%) or screen time (39.13%) as an index of SB and affect (39.14%) or life satisfaction (52.17%) as an outcome of hedonic well-being. All studies collected data quantitively, with the majority utilizing self-reported instruments for measuring indices of SB (79.31%). Conclusions: Overall, most studies demonstrated a weak, detrimental association between indices of SB and outcomes of hedonic well-being, however, this relationship varied depending on which index of SB was measured and how it was measured, with physical inactivity and screen time demonstrating stronger detrimental associations with outcomes of hedonic well-being. Future work should focus on measuring SB specifically, both device-based and self-reported, and including domain-specific SBs. Highlights: Sedentary behaviors demonstrate weak relationships with subjective well-being. More time spent sedentary or physically inactive is related to poorer well-being. Within-person differences in sedentary time may be more meaningful. Specific domains of sedentary time impact subjective well-being differently.